ANALISIS HAMBATAN IMPLEMENTASI KURIKULUM MERDEKA: STUDI KASUS PEMAHAMAN DAN KETERAMPILAN DIGITAL GURU - Fauziyah; Radeni Sukma Indra Dewi; Intan Sari Rufiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the barriers to the implementation of the Merdeka Curriculum and the role of elementary school teachers’ digital literacy using a Systematic Literature Review (SLR) approach. The review followed the PRISMA protocol and screened 312 articles from Scopus, Web of Science, ERIC, Google Scholar, and SINTA databases, resulting in 38 eligible articles for final analysis. The findings reveal four major themes hindering curriculum implementation: limited teachers’ curriculum literacy, low levels of digital literacy, a gap between instructional planning and classroom practice, and weak institutional and infrastructural support. The analysis also indicates that teachers’ understanding of learning outcomes, differentiation principles, and authentic assessment remains superficial, leading them to produce administrative teaching documents without internalizing the curriculum’s underlying philosophy. Low digital literacy further increases the complexity of these challenges, particularly regarding the use of pedagogical technologies, techno-anxiety, and limited access to digital devices in schools. In addition, a significant gap between lesson plan documentation and classroom implementation was identified, influenced by teachers’ pedagogical capacity and administrative workload. Limited institutional support, overly theoretical training, and unequal digital infrastructure serve as structural factors that reinforce these barriers. The synthesis of the SLR results emphasizes that successful implementation of the Merdeka Curriculum requires a systemic approach that integrates the strengthening of curriculum literacy, digital literacy, continuous professional development, as well as improvements in school facilities and evidence-based policy reforms to support instructional transformation in the Merdeka Belajar era.